Pengaruh Current Ratio (CR) dan Debt to Equity Ratio (DER) terhadap Harga Saham - Renaldi; Dharmawan, Donny; Syahribulan; Bakhtiar; Durya, Ngurah Pandji Mertha Agung (Jurnal EMT KITA, 2025)
The purpose of this study is to determine the effect of Current Ratio and Debt to Equity Ratio on the stock price of property sector companies listed on the IDX. The data used in this study are property sector companies from the IDX in 2018-2022 with 12 companies. The method used is regression analysis using SPSS 25.0. The research results show that CR and DER have no effect on the stock price of property sector companies. Adjusted R-squared score 0.4691 (46.91%). This indicates that the contribution of the current ratio, debt to equity ratio to the Stock Price is 46.91% and the remaining 53.09% is influenced by various other variables but are not analyzed in this research. The results of this research are expected to be useful for related institutions and investors in making decisions based on stock prices.